Integrating Khidmah and Tarbiyah: A Service-Learning Model in Indonesia’s Islamic Boarding School Education - Taisir, Muhammad; Sanusi, Ahmad; Aprillah, Ahmad (Al-Hayat: Journal of Islamic Education, 2025)
This study examines the Khidmah Tholabah program at Nurul Qur'an Praya Islamic Boarding School, an innovative model integrating community service into Islamic education. The research addresses three objectives: analyzing the program's conceptual foundations by blending Islamic pedagogy with service-learning theory, evaluating its sociological impact on local communities, and investigating student competency development. Using a qualitative case study approach, data was collected through in-depth interviews with 22 participants (4 administrators, 10 students, and 8 community members), participant observation across all program phases, and analysis of institutional documents and student reflection journals from March to April 2024. Findings reveal that the program's three-stage implementation framework successfully merges classical Islamic concepts like khidmah (service) and tarbiyah (holistic education) with experiential learning methodologies. Students developed enhanced religious understanding, teaching skills, and leadership capabilities through structured community engagement activities including Quranic instruction, Islamic lectures, and environmental clean-ups. The program strengthened community ties through reciprocal learning relationships and revived communal religious practices. The study’s originality lies in its detailed documentation of how traditional pesantren education can systematically incorporate service learning while maintaining religious authenticity. Key limitations include the single-site nature of the study and the relatively short observation period. The findings offer valuable insights for Islamic educators seeking to develop curriculum models that combine spiritual formation with social responsibility.